How Does the COVID-19 Crisis Affect Labor Demand? An Analysis Using Job Board Data From Austria - Omar Bamieh; Lennart Ziegler (Institute of Labor Economics (IZA), 2020)
This study uses data from the largest Austrian job board to examine labor-demand responses in the first months after the start of the COVID lockdown in March 2020. Our analysis shows that the number of job postings declined by a third and remained low even when implemented restrictions were loosened again. The decrease in labor demand affected all levels of education to a similar extent. For the remaining vacancies, we observe lower wage offers. Analyzing job descriptions of vacancy posts, we also find that employers became more likely to offer teleworking options. When we control for changes in occupations, estimates remain very similar, suggesting that the impact is not driven by an increase in the demand for teleworkable occupations. To test the robustness of our results, we merge two external occupation-level teleworking measures to our sample. Both measures are highly correlated with telework references in job ads and yield comparable estimates for the differential impact of the pandemic on labor demand.
Keywords: J23; J31; J61; J63; O33; R23; 330; job postings; telework; COVID-19